Kinetics analysis on isothermal torrefaction of sawdust in a fixed-bed reactor using the Coats-Redfern method and functional group analysis using FTIR spectroscopy / Alina Rahayu Mohamed, Noor Hasyierah Mohd Salleh and Nur Nadhirah Nordin - Mohamed, Alina Rahayu; Mohd Salleh, Noor Hasyierah; Nordin, Nur Nadhirah (Universiti Teknologi MARA Shah Alam, 2023)
In this study, torrefaction of sawdust was performed in a fixed bed reactor at different torrefaction temperatures and holding times of 200–300 °C and 20–60 mins respectively under inert nitrogen environment and isothermal condition. It was determined that the mass yield decreased upon increasing torrefaction temperature from 200 to 300 °C and holding time 20 to 60 mins. This could be contributed by the complete elimination of hemicellulosic fraction and slight removal of cellulosic fractions of sawdust which occurred at higher torrefaction temperature of 260–300 °C. The values of kinetics parameters such as activation energy, Ea and pre-exponential factor (ln A) for the torrefaction of sawdust at holding times of 20, 40, and 60 mins were evaluated using the Coats-Redfern method. The activation energy for torrefaction of sawdust reduced from 48.2054 to 41.7662 kJ/mol when the holding time for the reaction was increased from 20 to 60 mins. It was determined that the torrefaction of sawdust at 60 mins was more reactive than at 20 mins holding time. FTIR analysis on raw and torrefied sawdust showed the presence of OH hydroxyl group, C–H alkane, and C=O from ester or carboxylic acids groups.